Renal osteodystrophy and brown tumours of the jaw associated with tertiary hyperparathyroidism in the context of cystinosis: a case report - Sadeghi, Shayan; Bissada, Eric; Pertick, Nimaat (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Chronic kidney disease is one of the main manifestations of cystinosis that may lead to hyperparathyroidism. Although head and neck involvement in hyperparathyroidism is rare, lesions can occur in the jaws and cause serious functional handicap. We presented the case of a 24-year-old woman with congenital cystinosis and chronic renal failure complaining from symptomatic expansion of the jawbones. Medical imaging showed radiolucent lesions particularly in anterior hard palate and body of mandible. A diagnosis of renal osteodystrophy and brown tumours related to tertiary hyperparathyroidism was established. Following a subtotal parathyroidectomy and stabilization of parathyroid hormone levels, a conservative mandibular osteoplasty was undertaken to increase the available space for tongue movements. Although non-surgical management remains the primary modality for the treatment of brown tumours, adjunctive surgical approach may be considered in cases of severe functional impairment. It is imperative that underlying systemic imbalances be addressed prior to any maxillofacial intervention to prevent relapse.